The Role of Blockchain in Securing Internet of Things (IoT) Ecosystems: A Cross Industry Analysis - Mega Angkasa; Ika Rosalika; Dante Rio Sebastian; Beni Rahmatullah (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The rapid growth of the Internet of Things (IoT) has increased system connectivity across industries while simultaneously intensifying cybersecurity risks related to data integrity, access control, and system resilience. This study aims to analyze the role of blockchain technology in securing IoT ecosystems through a cross-industry perspective. A quantitative comparative approach was employed using a structured survey distributed to organizations in the manufacturing, healthcare, energy, logistics, and smart infrastructure sectors. Data were analyzed using descriptive and inferential statistical techniques to examine the effect of blockchain-based security mechanisms on IoT security performance. The findings indicate that blockchain adoption has a positive and significant impact on improving data integrity, strengthening access control, and enhancing system resilience across all observed industries. Variations in the strength of these effects reflect differences in regulatory pressure and operational risk among sectors. The results confirm that blockchain functions not only as a technical security solution but also as a strategic infrastructure for decentralized trust and risk governance in IoT environments. This study provides both theoretical contributions to IoT security frameworks and practical guidance for cross-sector blockchain implementation.